Ossetian-Ingush Mixed Jury Trial: Institutionalization of People’s Justice in Political and Legal Space of the Russian Empire - A. K. Abazov; R. M. Zhirov; A. A. Zhugov (Научный диалог)
The article analyzes the features of the institutionalization of the national justice of Ossetians and Ingush in the conditions of their incorporation into the political and legal space of the Russian Empire on the example of a mixed jury, which existed in 1908-1910. The place of a mixed jury trial in the judicial system of the Terek region in the early 20th century, in which both formal (state) and informal (people’s) institutions functioned, is considered. Such traditional institutions of socio-normative culture of the Ossetians and the Ingush applied in judicial practice, as compensation for the murder (“payment for blood”), infliction of wounds and injuries, theft, are described. Mutual responsibility as the main measure of responsibility for violation of the principles of social justice, as well as the oath and testimony of witnesses as a form of proof of guilt / innocence of the defendant are analysed in details. The principles of formation and replenishment of people’s cash registers, from which material compensation was paid to the injured party by the decision of the mixed court, were studied. It is concluded that the reception of the customs and traditions of Ossetians and Ingush by consolidating their people’s will in the Russian legal acts regulating the activities of the mixed court, retained the functional importance of national justice and laid the foundation for the formation of the subsequent Russian civil consciousness.